Green chromatographic method for analysis of some anti-cough drugs and their toxic impurities with comparison to conventional methods - Eglal A. Abdelaleem; Nada S. Abdelwahab (Elsevier, 2018)
Toxic solvents are widely used in chemical laboratories, which are dangerous on health, safety of workers, and environment. Green chemistry established different principles to keep safety of environment, one of these goals is to replace toxic solvents by greener alternatives or by minimizing the used volumes.Paracetamol (PAR), Guaifenesin (GUF), Oxomemazine (OX), and Sodium benzoate (SB) combination is a widely used cough preparation. 4- aminophenol (4-AP) is PAR poisonous impurity and related substance. Guiacol (GUC) is GUF impurity and related substance; its presence may lead to rejection of GUF sample.An eco-friendly HPTLC method was developed to quantify the studied drugs and their impurities. Chromatographic separation was achieved on HPTLC 60F254 plates using ethylacetate: methanol: 0.05 M ammonium chloride buffer (100: 2: 5, by volume) as a mobile phase and scanning at 225 nm. The linear ranges were 0.25-3.50, 0.50-8.00, 0.25-4.00, 0.20-8.00, 0.05-4.00, and 0.25-4.00 µg/band for PAR, GUF, OX and SB, 4-AP, and GUC. Method was successfully applied to available syrup and suppositories. It compared well with the reported method. It can be considered as an alternative green method for previously developed TLC method. Greenness profile of the method proved that it is greener than the reported methods being time and solvents saving. Keywords: Paracetamol, Guaifenesin, Oxomemazine, Sodium benzoate, 4-Aminophenol, Guiacol